Implementation Of The Kkn Gradasi Program (Mutual Cooperation, Academic Synergy, And Innovation) In Community Empowerment Of Mekarsari Village - Siti Aghniya; Siti Qoriah; Novita Dila Sari; Adelia Zahrani; Hana Nihayatussa Diyyah; Novia Keysa; Muchamad Ridwanudin Laili; Rita Puspita Sari; Nurzakiah Nurzakiah; Muhammad Ja’far Shiddiq; Rifaldi Ramadan; Muldani Muldani; Deden Abdul Hakim; Ali Hartono; Irsyad Nugraha (Fakultas Kewirausahaan Universitas Garut, 2026)
This study aims to analyze the implementation of the KKN GRADASI (Gotong Royong, Academic Synergy, and Innovation) Program in empowering the community of Mekarsari Village, Cilawu District, Garut Regency. The research object focuses on community empowerment activities implemented through education, economic and cultural development, health, and environmental management programs. This study employed a qualitative descriptive approach. Primary data were collected through direct observation, interviews with village officials, community leaders, UMKM actors, health cadres, and community members, as well as documentation of program implementation. Secondary data were obtained from village documents, KKN reports, and relevant literature. The results indicate that the implementation of the KKN GRADASI Program contributed positively to increasing community participation, strengthening students’ learning motivation, promoting local economic potential, enhancing public health awareness, and fostering environmental responsibility. These findings demonstrate that the KKN GRADASI Program serves as an effective community empowerment model through participatory and collaborative approaches.